2017
DOI: 10.5005/jp-journals-10015-1446
|View full text |Cite
|
Sign up to set email alerts
|

Root Coverage in Miller Classes I and II associated with Subepithelial Connective Tissue Graft: A comparative Clinical Trial of Two Techniques

Abstract: Introduction: Gingival recession is characterized by apical positioning of the gingival side in relation to the cementoenamel junction. Thus, this study aimed at evaluating the effectiveness of two surgical techniques for root coverage in patients with gingival recession of Miller class I or II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Due to these advantages, already well established in the literature, it was used in this study associated to Tunnel and CPF surgical techniques. When these two techniques were compared in Miller class I and II recessions, researchers obtained effective outcomes in both techniques [22]. While comparing its use in RT2 recessions, good effectiveness and similar outcomes across the parameters analyzed after use of these techniques were observed (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Due to these advantages, already well established in the literature, it was used in this study associated to Tunnel and CPF surgical techniques. When these two techniques were compared in Miller class I and II recessions, researchers obtained effective outcomes in both techniques [22]. While comparing its use in RT2 recessions, good effectiveness and similar outcomes across the parameters analyzed after use of these techniques were observed (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 84%
“…According to the literature, after 5 months of root coverage with the surgical techniques used in this study, some level of regeneration in periodontal defects can be observed, and formation of new cement, alveolar bone, and periodontal ligament can be obtained, as well as large portions of the root covered by connective tissue and long junctional epithelium [22,[30][31][32]. Though CPF + SCTG present better outcomes in periodontal parameters, they are not statistically significant, demonstrating that both techniques can be recommended for the treatment of RT2 recessions in patients.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The calculation of the sample size to the number of gingival recessions was made with t-test for independent samples with test power of 80% and alpha level of 0.05. These data were based on previous studies of the researchers group [16,17,18].…”
Section: Methodsmentioning
confidence: 99%